Extracellular Antifreeze Protein Significantly Enhances the Cryopreservation of Cell Monolayers - Tomás, Ruben M. F. (Biomacromolecules, 2019)
[Image: see text] The cryopreservation of cells underpins many areas of biotechnology, healthcare, and fundamental science by enabling the banking and distribution of cells. Cryoprotectants are essential to prevent cold-induced damage. Here, we demonstrate that extracellular localization of antifreeze proteins can significantly enhance post-thaw recovery of mammalian cell monolayers cryopreserved using dimethyl sulfoxide, whereas they show less benefit in suspension cryopreservation. A type III antifreeze protein (AFPIII) was used as the macromolecular ice recrystallization inhibitor and its intra/extracellular locations were controlled by using Pep-1, a cell-penetrating peptide. Flow cytometry and confocal microscopy confirmed successful delivery of AFPIII. The presence of extracellular AFPIII dramatically increased post-thaw recovery in a challenging 2-D cell monolayer system using just 0.8 mg·mL(–1), from 25% to over 60%, whereas intracellularly delivered AFPIII showed less benefit. Interestingly, the antifreeze protein was less effective when used in suspension cryopreservation of the same cells, suggesting that the cryopreservation format is also crucial. These observations show that, in the discovery of macromolecular cryoprotectants, intracellular delivery of ice recrystallization inhibitors may not be a significant requirement under “slow freezing” conditions, which will help guide the design of new biomaterials, in particular, for cell storage.